Truth in publishing : federal regulation of the press's business practices, 1880-1920 - Lawson, Linda, 1952- (Southern Illinois University Press, 1993)
This is the first policy history to examine government regulation of the print media's business practices in the early twentieth century. Most media histories depict the early twentieth-century press as a crusader, working closely with reformers to weed out abuses in society. This book turns the tables and examines the press as a business susceptible to corporate abuses and government regulation - just like any other enterprise. And like other business leaders targeted by reformers, some publishers and advertisers welcomed the scrutiny of reformers and encouraged lawmakers to enact strong legislation to cleanse the profession. Others, however, tried to hide behind the First Amendment and resisted all attempts at government regulation. In the end, Congress bypassed the First Amendment question by linking its regulations to the press's mail privilege, where, it was felt, the courts would uphold its authority to set standards for the subsidy. The Newspaper Publicity Act, passed in 1912, is still in effect and requires commercial newspapers and magazines using the preferential second-class mail rate to identify their owners and investors and to label advertisements that resemble news stories or editorials. These publications are also required to disclose circulation data along with their ownership statements. In part 1, Linda Lawson documents the press's inner workings, including its excesses and abuses, as it evolved from a collection of small businesses in the mid-1800s to an established commercial institution of the twentieth century. Large, urban newspapers challenged small, rural papers at the same time burgeoning popular magazines and trade journals competed fiercely with every other type of publication for advertisers and readers. The regulatory actions brought about by these divisions within the industry are treated in part 2. Lawson makes clear how Congress, the post office, and the courts responded to the troubling business practices outlined in part 1. Finally, she analyzes what this episode in policy making reveals about Progressive ideology's reliance on publicity and regulation to solve social and economic problems; in the process, Lawson integrates many of the apparently paradoxical strands of scholarship on the Progressive period.